The Long-Term Impact of Polysaccharide-Coated Iron Oxide Nanoparticles on Inflammatory-Stressed Mice - Julia Göring; Claudia Schwarz; Eric Unger; Rainer Quaas; Ingrid Hilger (Journal of Xenobiotics)
Since iron oxide nanoparticles (IONPs) are expected to be important tools in medical care, patients with inflammatory diseases will be increasingly exposed to IONPs in the future. Here, we assessed the short- and long-term impact of polysaccharide (PS)-coated IONPs on mice with persistent systemic inflammation. To this end, PS-IONPs were synthetized by a core-shell method. Mice were regularly injected with sterile zymosan. PS-IONPs were administered intravenously. At specific nanoparticle injection post-observation times, the organ iron concentration was determined via atomic absorption spectrometry, the expression of NF-κB-related proteins using SDS-PAGE and immunoblotting, as well as body weight and haemograms. Finally, the mediator secretion in blood plasma was analysed using multiplexed ELISA. Our data show that PS-IONPs induce short-term changes of iron levels in distinct organs and of NF-κB p65 and p50, p100, COX-2s, and Bcl-2 protein expression in the liver of inflammatory stressed mice. In the long term, there was an attenuated expression of several NF-κB–related proteins and attenuated features of inflammatory-based anaemia in blood. PS-IONPs weakly influenced the blood cytokine levels. PS-IONPs are biocompatible, but given their short-term pro-inflammatory impact, they should prospectively be applied with caution in patients with inflammatory diseases of the liver.